Neuropsychological profile of CSF1R-related leukoencephalopathy - Rush, Beth K.; Tipton, Philip W.; Strongosky, Audrey; Wszolek, Zbigniew K. (Frontiers in Neurology, 2023)
Introduction The neuropsychological profile of CSF1R-related leukoencephalopathy (CRL) is undefined. This study defines the profile, contrasts it with that of other dementia syndromes, and highlights measures sensitive to cognitive impairment. Methods We administered a standardized battery of neuropsychological tests to five consecutive CRL cases. Results The neuropsychological profile of CRL reflects impaired general cognitive function, processing speed, executive function, speeded visual problem solving, verbal fluency, and self-reported depression and anxiety. Confrontation naming and memory are preserved. Within cognitive domains, certain measures more frequently identified impairment than others. Discussion CRL impairs general cognitive function, processing speed, executive function. Language and visual problem solving may be impaired if processing speed is required. Confrontation naming and memory are uniquely preserved, contrasting CRL to other dementia syndromes. Cognitive screens excluding processing speed and executive function may not detect CRL cognitive manifestations. Findings sharply define cognitive impairment of CRL and inform cognitive test selection.